A31 DISPARITIES IN THE CARE OF RURAL AND URBAN CANADIANS WITH INFLAMMATORY BOWEL DISEASE: A POPULATION-BASED STUDY - Benchimol, E I (J Can Assoc Gastroenterol, 2018)
BACKGROUND: Canada’s large geographic area and low population density poses challenges in access to specialized healthcare for remote and rural residents. Inflammatory bowel disease (IBD) (Crohn’s disease (CD) and ulcerative colitis (UC)) is less common among rural residents, however disparities in care and outcomes may exist. AIMS: Compare health services use and markers of disease control (hospital admissions and surgeries) in rural and urban IBD patients in Canada using population-based health administrative data. METHODS: Validated algorithms identified all incident cases of IBD from administrative data in 3 provinces: Alberta (AB) 1999–2008, Manitoba (MB) 1999–2010, Ontario (ON) 1999–2010. We compared rural to urban residents for time to diagnosis, IBD-specific hospitalization, outpatient visits, emergency department (ED) use (ON only), surgical resections (CD) or colectomy (UC), and gastroenterologist (GI) care. Rural/urban status was based on Metropolitan Area and Census Agglomeration Influenced Zones. Multivariable regression compared outcomes in rural/urban residents, controlling for confounders (Table footnote). Provincial results were meta-analyzed to produce overall estimates. RESULTS: See Table. 37,018 urban and 6656 rural residents with incident IBD were included. Rural patients had fewer GI visits, and a smaller proportion of their IBD-specific care provided by GI (39.1% vs 61.4%, P<0.0001). Rural patients were more frequently hospitalized, and used the ED more. There was no difference in outpatient visit rate or risk of first surgery. However, rural patients were more likely to undergo multiple intestinal resections. CONCLUSIONS: Rural IBD patients have less use of GI specialists and more need for acute care, suggesting worse outcomes related to disparities in access to specialist care. Innovative methods of delivering GI care to rural IBD patients (such as telehealth, online support, remote clinics) should be explored. FUNDING AGENCIES: CIHRJanssen Future Leaders in IBD Grant, CHEO Research Institute